Cerebellar neuronal dysfunction accompanies early motor symptoms in spinocerebellar ataxia type 3 - Kristin Mayoral-Palarz; Andreia Neves-Carvalho; Sara Duarte-Silva; Daniela Monteiro-Fernandes; Patrícia Maciel; Kamran Khodakhah (The Company of Biologists, 2022)
Spinocerebellar ataxia type 3 (SCA3) is an adult-onset, progressive ataxia. SCA3 presents with ataxia before any gross neuropathology. A feature of many cerebellar ataxias is aberrant cerebellar output that contributes to motor dysfunction. We examined whether abnormal cerebellar output was present in the CMVMJD135 SCA3 mouse model and, if so, whether it correlated with the disease onset and progression. In vivo recordings showed that the activity of deep cerebellar nuclei neurons, the main output of the cerebellum, was altered. The aberrant activity correlated with the onset of ataxia. However, although the severity of ataxia increased with age, the severity of the aberrant cerebellar output was not progressive. The abnormal cerebellar output, however, was accompanied by non-progressive abnormal activity of their upstream synaptic inputs, the Purkinje cells. In vitro recordings indicated that alterations in intrinsic Purkinje cell pacemaking and in their synaptic inputs contributed to abnormal Purkinje cell activity. These findings implicate abnormal cerebellar physiology as an early, consistent contributor to pathophysiology in SCA3, and suggest that the aberrant cerebellar output could be an appropriate therapeutic target in SCA3.